TEACHING READING NARRATIVE TEXT USING STELLER THROUGH SIGNAL GROUP - Anita Anggraeni (PROJECT (Professional Journal of English Education), 2022)
The purpose of this study was to understand the scenario and implementation of learning to read Narrative Text. using Steller through Signal Group, to find out teacher and student responses, as well as teacher and student barriers to the implementation of teaching scenarios during online learning during the covid pandemic. This research uses a qualitative descriptive method. The participants in this study were students of class X in one of the Vocational Schools in Cimahi and an English teacher. The instruments in this study were questionnaires, observation sheets, teacher field notes, and tests. Based on research in the field, data obtained that the scenario and implementation of the teaching scenario went well and also received positive responses from both students and teachers. The difficulty experienced by most students is understanding the purpose of the text and looking for references. Another obstacle faced by teachers was technical problems with the Steller application, while student barriers were prerequisite skills 61.33%, time/interruption 70%, motivation 71.7%, technical 76.8% and social 83.7% which showed that all the obstacles faced by most of the students are not too annoying but the unstable internet connection and storage space of the device. Thus, the writers conclude that the use of Steller in this study can help the implementation of learning to write Narrative Text. In addition, teachers can also create appropriate learning media on the Steller teacher story page, especially for teaching reading Narrative Text. However, the teacher must estimate the obstacles that may occur during the activity, especially for technical problems that may occur. Keywords:  Reading, Narrative Text,, Steller, Signal Group